A Distributed Reclustering Hierarchy Routing Protocol Using Social Welfare in Wireless Sensor Networks. (11th April 2012) - Yang, Pu-Tai; Lee, Seokcheon
Abstract : In recent years, there has been a rapid proliferation of research concerning Wireless Sensor Networks (WSNs), due to the wide range of potential applications that they can be used for. Lifetime is one of the most important considerations for WSNs due to their inherent energy constraints, and various protocols have been proposed to overcome these difficulties. This study proposes a novel distributed reclustering routing protocol: Predictive and Adaptive Routing Protocol using Energy Welfare (PARPEW). PARPEW incorporates the concept of energy welfare (EW) to achieve both energy efficiency and energy balance simultaneously. PARPEW is equipped with a cluster head (CH) shift mechanism that utilizes predictive energy after transmission for the computation of EW. The average case time complexity of the shift mechanism belongs to O ( | C | 2 ), where | C | is the average number of sensors in a cluster in the WSN. Experimental results demonstrate that the new protocol is capable of significantly prolonging the lifetime of WSNs under various scenarios.